The Incidence of Postoperative Seizures Following Treatment of Postinfectious Hydrocephalus in Ugandan Infants: A Post Hoc Comparison of Endoscopic Treatment vs Shunt Placement in a Randomized Controlled Trial. Issue 7 (16th November 2020) - Punchak, Maria; Kabachelor, Edith Mbabazi; Ogwal, Michael; Nalule, Esther; Nalwoga, Joyce; Ssenyonga, Peter; Mugamba, John; Rattani, Abbas; Dewan, Michael C; Kulkarni, Abhaya V; Schiff, Steven J; Warf, Benjamin
Graphical Abstract: